piR-26441 inhibits mitochondrial oxidative phosphorylation and tumorigenesis in ovarian cancer through m6A modification by interacting with YTHDC1 - Jing Yuan; Bu-Min Xie; Yu-Meng Ji; Hai-Juan Bao; Jie-Lin Wang; Jia-Chen Cheng; Xiang-Chun Huang; Yang Zhao; Shuo Chen (Cell Death and Disease)
Abstract Ovarian cancer (OC) is a heterogeneous cancer. In contrast to other tumor cells, which rely primarily on aerobic glycolysis (Warburg effect) as their energy source, oxidative phosphorylation (OXPHOS) is also one of its major metabolic modes. Piwi-interacting RNAs (piRNAs) play a regulatory function in various biological processes in tumor cells. However, the role and mechanisms of piRNAs in OC and mitochondrial OXPHOS remain to be elucidated. Here, we found that piR-26441 was aberrantly downregulated in OC, and its overexpression suppressed the malignant features of OC cells and tumor growth in a xenograft model. Moreover, overexpression of piR-26441 significantly reduced mitochondrial OXPHOS levels in OC cells. Furthermore, piR-26441 directly binds to and upregulates the expression of YTHDC1 in OC cells. piR-26441 also increased m6A levels, thereby interacting with YTHDC1 to destabilize the mRNA of TSFM. The resultant TSFM loss reduced mitochondrial complex I activity and mitochondrial OXPHOS, leading to mitochondrial dysfunction in OC cells, increased reactive oxygen species levels, and thus, DNA damage and apoptosis in OC cells, thereby inhibiting OC progression. Additionally, ago-piR-26441 suppressed tumor growth and mitochondrial metabolism in the patient-derived organoid model. Altogether, piR-26441 could inhibit OC cell growth via the YTHDC1/TSFM signaling axis, underscoring its significant importance in the context of OC, as well as offering potential as a therapeutic target.